Cardiovascular Risks and Outcomes Among Chinese American Immigrants: Insights From the Multi‐Ethnic Study of Atherosclerosis - Xinjiang Cai; Quinn White; Daniel R. Wang; Christopher R. DeFilippi; Alain G. Bertoni; Colin O. Wu; Kiang Liu; Joao A. C. Lima; Matthew J. Budoff; Gregg C. Fonarow; Karol E. Watson; Robyn L. McClelland; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Immigrants experience changes in cardiovascular risk factors and racial disparities in both cardiovascular health prevention and outcomes upon immigration. We aimed to examine cardiovascular risk factors and outcomes among Chinese American immigrants enrolled in the MESA (Multi‐Ethnic Study of Atherosclerosis) cohort. Methods and Results We analyzed data from 746 Chinese American immigrants in the MESA study with a median follow‐up period of 17.8 years. The mean age of the cohort was 62.3 years, with 52.7% being women. Kaplan–Meier curves and Cox proportional hazards models were used to assess the association of immigration history, geographic location, biomarkers, and cardiac imaging parameters with cardiovascular risk factors and cardiovascular outcomes. The Cox hazards models were adjusted for known family history of heart disease, education level, sex, diabetes, hypertension, age, and body mass index. Although immigration history categorized as earlier (<20 years) versus later (≥20 years) showed no association with cardiovascular outcomes, the duration of residence in the United States emerged as a strong predictor for an increased risk of cardiovascular disease death (hazard ratio 1.39 [95% CI, 1.07–1.8]; P=0.012). All‐cause mortality differed significantly between the Chinese immigrants from Los Angeles and those from Chicago, with higher survival probability in Chicago (log‐rank test, P=0.018). Furthermore, elevated levels of N‐terminal pro‐brain natriuretic peptide levels, left ventricular mass, and coronary artery calcium scores were associated with the risk of cardiovascular disease among Chinese immigrants. Conclusions Within the MESA cohort, the duration of residence and geographic location were associated with the risk of cardiovascular disease outcomes among Chinese immigrants.